A Novel Digital Technique to Analyze the Wear of CM-Wire NiTi Alloy Endodontic Reciprocating Files: An In Vitro Study - Faus Matoses, Vicente; Faus Llácer, Vicente; Aldeguer Muñoz, Álvaro; Alonso Pérez-Barquero, Jorge; Faus Matoses, Ignacio; Ruiz Sánchez, Celia; Zubizarreta Macho, Álvaro (My University, 2022)
Abstract: The present study seeks to describe a novel digital measurement technique for analyzing the wear volume of controlled memory (CM)-wire NiTi alloy endodontic reciprocating files after clinical use. Material and Methods: Ten CM-wire NiTi endodontic reciprocating files were randomly used in ten first upper molar teeth within four root canals. The CM-wire NiTi alloy endodontic reciprocating files were subjected to preoperative and postoperative micro-computed tomography (micro-CT) scans to obtain accurate digital imaging and communication on medicine (DICOM) digital files, which were segmented using intensity-based thresholding and an exclusive OR (XOR) logical operation (Boolean algebra logical operator) to obtain a mask of the location to localize and quantify the wear volume of the CM-wire NiTi alloy endodontic reciprocating files. Gage repeatability and reproducibility statistical analysis was applied to assess the reproducibility and repeatability of this measurement technique. Results: The analysis showed a repeatability and reproducibility of 0.00% for the digital measurement technique used to analyze the wear volume of CM-wire NiTi alloy endodontic reciprocating files after clinical use. Wear was mostly identified at the tip and cutting edges of the CM-wire NiTi alloy endodontic reciprocating files. Conclusions: This novel digital measurement technique is a repeatable, reproducible, and accurate method of quantifying the wear volume of CM-wire NiTi alloy endodontic reciprocating files after clinical use. Keywords: endodontics; cyclic fatigue; wear; NiTi; reciprocating movement; micro-computed tomography